EXPERIMENTAL MEASUREMENTS OF THE PROPERTIES OF H2O-CO2 MIXTURES AT HIGH PRESSURES AND TEMPERATURES - Frost D.J.; Wood B.J. (My University, 1997)
We have experimentally determined volumes of H2O-CO2 mixtures between 9.5 and 19.4 kbar at 1100-1400°C. A synthetic fluid inclusion technique (Sterner and Bodnar, 1991) was used to capture H2O-CO2 fluids of known composition in precracked corundum. The densities of the fluids were determined from measurements of the homogenization temperatures along the CO2 liquid-vapour equilibrium curve. The experimentally determined volumes show good agreement with the MRK equation of state of Holloway (1977) for mole fractions of CO2 less than 0.5.Further results are reported for the volume of pure water at 14.5 kbar and 1000-1400°C, determined from fluid inclusion experiments of the type described by Brodholt and Wood (1994). These results were used to derive an equation of state applicable to the calculation of H2O PVT properties in the range 1-80000 bar and 800-1600°C. This new equation and the equation of state of Frost and Wood (1997) for CO2 were used to determine excess volumes for H2O-CO2 mixtures. Over the range of experimental conditions, H2O-CO2 fluids show small positive deviations from ideal mixing, with excess volumes that are greater than 0.6 cc/mol.